Acute T-cell lymphoblastic leukemia: chimeric antigen receptor technology may offer a new hope - Jing, Jiajie; Ma, Yuan; Xie, Ziwen; Wang, Bingyan; Chen, Yueming; Chi, Enjie; Wang, Jiadong; Zhang, Kejin; Wang, Zhujun; Li, Sisi (Frontiers in Immunology, 2024)
Acute lymphoblastic leukemia (ALL) is a prevalent malignancy affecting the hematopoietic system, encompassing both B-cell ALL (B-ALL) and T-cell ALL (T-ALL). T-ALL, characterized by the proliferation of T-cell progenitors in the bone marrow, presents significant treatment challenges, with patients often experiencing high relapse rates and poor long-term survival despite advances in chemotherapy and hematopoietic stem cell transplantation (HSCT). This review explores the pathogenesis and traditional treatment strategies of T-ALL, emphasizing the promising potential of chimeric antigen receptor (CAR) technology in overcoming current therapeutic limitations. CAR therapy, leveraging genetically modified immune cells to target leukemia-specific antigens, offers a novel and precise approach to T-ALL treatment. The review critically analyzes recent developments in CAR-T and CAR-NK cell therapies, their common targets, optimization strategies, clinical outcomes, and the associated challenges, providing a comprehensive overview of their clinical prospects in T-ALL treatment.